2015
DOI: 10.21608/bvmj.2015.31872
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological aspect of meat and poultry meat meals

Abstract: Ninety random samples were collected from different restaurants in Benha city to evaluate their bacteriological quality. The mean values of APC, coliform, staphylococcus counts (cfu /g) were 2.69x 10 5  0.47x10 5 , 5.54x10 3  0.96x10 3 & 2.31 x 10 3  0.49 x 10 3 for beef kofta,7.34x10 4  1.22x10 4 , 1.73x10 3  0.51x10 3 &1.57 x 10 3  0.36x 10 3 for beef burger, 3.16x 10 4  0.60 x 10 4 , 1.01 x 10 3 0.27 x 10 3 & 6.29 x 10 2  1.14x10 2 for beef shawerma, 6.23 x 10 5  1.14x10 5 , 8.52x10 3  2.04x10 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…The illustrated results in table (1) revealed that the Staphylococci counts(cfu/g) in the examined samples of beef burger agree with those obtained by Hassanien et al (2015) "1.57 x 10 3 ±0.36x 10 3 ", while the lower results were recorded by Ragab et al (2016) "4x 10 2 "and the higher results recorded by Ibrahim (2016) "2.08 х10 5 ± 5.56 х10 4 ".…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The illustrated results in table (1) revealed that the Staphylococci counts(cfu/g) in the examined samples of beef burger agree with those obtained by Hassanien et al (2015) "1.57 x 10 3 ±0.36x 10 3 ", while the lower results were recorded by Ragab et al (2016) "4x 10 2 "and the higher results recorded by Ibrahim (2016) "2.08 х10 5 ± 5.56 х10 4 ".…”
Section: Discussionsupporting
confidence: 75%
“…The results of kofta samples were similar to those obtained by EL-Hanafy (2016) "40%". while the lower results were recorded by Hassanien (2004) "24%" and highter results recorded by Hassanien et al (2015) "60%".…”
Section: Discussionmentioning
confidence: 76%
“…Microbiological assessment on safety, storage stability, and sanitary quality of traditional meat products were carried out to analyses for the presence of some pathogens like Staphylococcus aureus, different microbial groups (e.g., Total Viable Counts and yeast and molds), and indicator bacteria (e.g., E. coli as an indicator of sanitation). The variation in bacterial count between different types of meat products could be attributed to difference of ingredients and steps involved in their formulation and preparation [7].…”
Section: Introductionmentioning
confidence: 99%